Effect of a free healthcare policy on health services utilisation for non‐malarial febrile illness by children under five years in Burkina Faso: an interrupted time series analysis. Issue 10 (5th August 2020) - Sia, D.; Dondbzanga, B. D. G.; Carabali, M.; Bonnet, E.; Enok Bonong, P. R.; Ridde, V.
Abstract: Objective: To assess the effect of a free healthcare policy for children under five years old implemented in Burkina Faso since April 2016, on the use of health care of non‐malarial febrile illnesses (NMFI). Methods: To assess the immediate and long‐term effect of the free healthcare policy in place, we conducted an interrupted time series analysis of routinely collected data on febrile illnesses from three urban primary health centres of Ouagadougou between 1 January 2015 and 31 December 2016. Results: Of the 39 046 febrile cases reported in the study period, 17 017 NMFI were included in the study. Compared to the period before the intervention, we observed an immediate, non‐statistically significant increase of 7% in the number of NMFI (IRR = 1.07; 95% CI = 0.75, 1.51). Compared to the trend that would have been expected in absence of the intervention, the results showed a small but sustained increase of 6% in the trend of monthly number of NMFI during the intervention period (IRR = 1.06; 95%CI = 1.01, 1.12). Conclusion: Our study highlighted an increase in the uptake of healthcare services, specifically for NMFI by children under five years of age, after the implementation of a free care policy. This analysis contributes to informing decision makers on the need to strengthen the capacities of healthcare centres and to anticipate the challenges of the sustainability of this policy. Abstract : Objectif: Evaluer l'effet d'une politique de gratuité des soins pour les enfants de moins de cinq ans mise en œuvre au Burkina Faso depuis avril 2016, sur l'utilisation des soins de santé des maladies fébriles non paludiques (MFNP). Méthodes: Pour évaluer l'effet immédiat et à long terme de la politique de gratuité des soins en place, nous avons mené une analyse des données de séries chronologiques interrompues collectées en routine sur les maladies fébriles dans trois centres de santé primaires urbains de Ouagadougou entre le 1 er janvier 2015 et le 31 décembre 2016. Résultats: Sur les 39.046 cas fébriles signalés au cours de la période d'étude, 17.017 MFNP ont été inclus dans l'étude. Par rapport à la période précédant l'intervention, nous avons observé une augmentation immédiate et non statistiquement significative de 7% du nombre de MFNP (IRR = 1, 07; IC95%: 0, 75 à 1, 51). Par rapport à la tendance à laquelle on aurait pu s'attendre en l'absence d'intervention, les résultats ont montré une augmentation faible mais soutenue de 6% de la tendance du nombre mensuel de MFNP pendant la période d'intervention (TRI = 1, 06; IC95%: 1, 01 à 1, 12 ). Conclusion: Notre étude a mis en évidence une augmentation de l'utilisation des services de santé, en particulier pour les MFNP pour les enfants de moins de cinq ans, après la mise en œuvre d'une politique de gratuité des soins. Cette analyse contribue à informer les décideurs sur la nécessité de renforcer les capacités des centres de santé et d'anticiper les enjeux de la pérennité de cette politique.